PENGARUH BIAYA PEMELIHARAAN TERHADAP PENDAPATAN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2024 - Rukmi Juwita; Restu Nurjanah (LAND JOURNAL, 2026)
Revenue fluctuated at several automotive and component manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. Several causes contributed to this fluctuation, including maintenance costs related to production factors. This study purpose to confirm and examine how Maintenance Costs affect Revenue, and the difference in maintenance costs and revenue in automotive and companies manufacturing on the IDX For The 2020-2024 Period. The methodology used in this study is quantitatitve. There are 30 financial reports of Automotive and Component Sub Sector Manufacturing Companies on The IDX which are the populations in this research, purposive sampling was used in the sample selection process. The calibration uses statistical test including Normality Test, Product Moment Correlation, Simple Regression Linier, Coefficient of Determination, and t-Test. The results of the difference of maintenance cost and revenue For The 2020-2024 Period experienced fluctuations. Based on the findings of the hypothesis test that Maintenance Cost significantly and favorably affect on Revenue in Automotive and Component Manufacturing Companies Listed On The IDX For The 2020-2024 Period.